ANALISIS PENGENDALIAN INTERN TERHADAP PENGENDALIAN PIUTANG TAK TERTAGIH PADA PT. TELKOM INDONESIA Tbk. MAKASSAR - Irwandi, Syahrul; Jumarti, Jumarti; Azis, Nur Alimin; Iskandar, Sultan (Universitas Patria Artha, 2024)
This study was aimed at analyze of internal Control on Uncollectible Accounts at PT. TelkomIndonesia Tbk in Makassar. The data used were primary and secondary data. Data collectiontechniques used were observation, interviews, questionnaires, documentation. The data analysis technique used were data validity test, data test, hypothesis test, partial test, instrument reliability test. The result of this study indicated that in internal control influenced positive and significantly on the control of uncollectible accounts at PT. Telkom Indonesia Tbk Makassar.